Protective mechanism of quercetin nanoliposomes on hydrogen peroxide-induced oxidative damage in 3D Caco-2 cell model - Xiaofeng Liu; Zhiyuan Zhou; Xiaoqin Lu; Hao Zhong; Rongjun He; Ziwei Feng; Rongfa Guan (Journal of Functional Foods)
Quercetin is a flavonol that is widely distributed in plants. Although quercetin has good antioxidant activity, the exact mechanism is still unclear in intestinal cell model. In this study, a 3D Caco-2 cell model was constructed. An oxidative damage model was then established. Compared with 2D cell models, 3D cell models are more similar to the in vivo microenvironment and more sensitive to external stimuli. Quercetin and its nanoliposomes significantly increased intracellular SOD, GSH-Px and CAT activity and the T-AOC, and reduced ROS, IL-8 and MDA levels to exert antioxidant effects (P < 0.05). Moreover, the antioxidant effect of the quercetin nanoliposomes was superior to that of quercetin. Quercetin nanoliposomes can regulate the oxidative genes HO-1, Keap1, and Nrf2, activating downstream antioxidant enzymes and upregulating GST, NQO1, and Keap1 protein expression. Quercetin nanoliposomes protect cells from oxidative stress through the Nrf2 pathway.